ANALISIS PENGARUH KEPEMIMPINAN OTENTIK DAN SELF-EFFICACY TERHADAP KINERJA PRAJURIT DENGAN LOYALITAS SEBAGAI VARIABEL INTERVENING PADA SATKAT KOARMADA II SURABAYA - Siswanto, Arif; Prasetyo, Indra (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2025)
This study aims to analyze the Influence of Authentic Leadership and Self-Efficacy on Soldier Performance with Loyalty as an Intervening Variable in the Surabaya Second Fleet Task Force. The population in this study is 178 officers serving in the Surabaya Koarmada II Task Force. This type of research is an explanatory with a quantitative approach. The sampling technique used in this study was determined as many as 25 times the indented variable. In this study, the number of indented variables is three variables, so the number of samples in this study is 75 respondents. The data analysis technique of this study uses SEM-PLS. The results of the study show that the authentic leadership have a significant effect on loyalty, authentic leadership is proven to have a positive effect on loyalty. The authentic leadership have a significant positive effect on soldier performance, self-efficacy have a significant positive effect on soldier performance, loyalty is proven to have an effect on the performance of soldiers. The indirect influence test shows that the authentic leadership is proven to have a significant positive effect on soldier performance through loyalty, self-efficacy have a significant positive effect on soldier performance through loyalty.